ANALISIS PROBLEMATIKA SIDE STREAMING PADA PEMBIAYAAN MURABAHAH BIL WAKALAH DI PERBANKAN SYARIAH - Ismawati Khasanah; Mauliana Fauziyah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
Murabaha financing is a superior product in Islamic banking which is included in buying and selling contracts. After experiencing the development and modification of murabahah financing, it is now better known as murabahah bil wakalah. The purpose of this study is to find out the problems that exist in the murabahah bil wakalah contract, namely the occurrence of side streaming actions. This study uses a qualitative method with a literature study where data are taken from sources derived from literature such as books, articles, and other sources. Murabahah bil wakalah contract is a sale and purchase contract in which the Islamic bank gives power or represents to the customer to purchase the object of self-financing from the supplier. With the power granted this creates some problems that can damage or invalidate the contract, such as side streaming actions. Side streaming is an act of using funds that is not in accordance with the contract, Â so this action is considered a form of deviation and includes a fake contract. Customers tend to be more flexible in buying the desired goods, such as on behalf of the buyer from the supplier, not on behalf of the bank. Other side streaming actions can be in the form of price differences that have been agreed upon, and cause non-performing financing and a decrease in the collectability of Islamic banks.Keywords: Murabahah bil Wakalah, Side Streaming, Islamic BankingÂ